(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
With the decision on the “Cappato case” the Constitutional Court did not create the right to medically assisted suicide, which, moreover, the constitutional order does not contemplate, but only identified a “circumscribed area” of unconstitutionality of art. 580 of the Italian Criminal Code, supporting it with regulatory and procedural props. In this way, the Court demonstrated its self-restraint respectful of Parliament’s discretion and underlined the persistence of the need for legislative intervention in such a sensitive matter.